2004
DOI: 10.1002/jsc.666
|View full text |Cite
|
Sign up to set email alerts
|

Culturally tuned emotional intelligence: an effective change management tool?

Abstract: ᭹ This article is concerned with the potential influence of culture in managing emotions both in others and in ourselves, within a change management framework. ᭹ It is proposed that reframing emotional intelligence (EI) in terms of culture may support leaders when effecting change within their organizations. ᭹ For well over a decade anthropologists have suggested that cultures have conventions and norms that influence the management of emotions. ᭹ Cultural values create a commonality among members in how they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Emotional intelligence of the employee was found to be positively related to employee attitude towards change as well as to facilitate the change process (Vakola and Nikolaou, 2005;Chrusciel, 2006). As per Herkenhoff (2004), another common area of change within organizations involves seeking higher levels of employee initiative and innovation. Creative people not just adapt easily to change but are also more likely to lead it.…”
Section: Antecedents Of Readiness For Change Individual Factor: Intelmentioning
confidence: 99%
“…Emotional intelligence of the employee was found to be positively related to employee attitude towards change as well as to facilitate the change process (Vakola and Nikolaou, 2005;Chrusciel, 2006). As per Herkenhoff (2004), another common area of change within organizations involves seeking higher levels of employee initiative and innovation. Creative people not just adapt easily to change but are also more likely to lead it.…”
Section: Antecedents Of Readiness For Change Individual Factor: Intelmentioning
confidence: 99%
“…The strongest research stream supporting the applicability of EI in organizations is that of leadership, where high correlations have been found between EI and performance (Cavallo & Brienza, 2008; Chrusciel, 2006; Daus & Ashkanasy, 2005; L. Gardner & Stough, 2002; Goleman; 1998a; Goleman, Boyatzis, & McKee, 2002; Herkenhoff, 2004; Kerr et al, 2006; Sy & Cote, 2004). Studies using EI tools have found relationships with an individual's ability to handle stress (Bachman, Stein, Campbell, & Sitarenios, 2000; Chrusciel, 2006; Humphrey, Curran, Morris, & Woods, 2006; Lusch & Serpkeuci, 1990; Seligman, 1990), create sales growth or recruit effectively (Bar‐On, 2004; Cherniss & Adler, 2008; Goleman, 1998a; Luskin, Aberman, & DeLorenzo, 2008; Pilling & Eroglu, 1994; Spencer, McClelland, & Kelner, 1997; Spencer & Spencer, 1993), reduce turnover in their teams or themselves (Daus & Ashkanasy, 2005; Leslie & Van Velsor, 1996; McClelland, 1999; Stephens, 2007; Tucker, Sojka, Barone, & McCarthy, 2000), and build effective or productive relationships at work (Book, 2000; Caruso & Wolfe, 2002; Goleman, 1998b, 2001), among others.…”
Section: Emotional Intelligencementioning
confidence: 99%
“…In that regard, and as a complement to the knowledge boundary-spanning effects of EI, culture has tremendous influence on emotional process: "Culture…. Influences the selection of an action or behavior as a response to the event" (Herkenhoff, 2004). Danaeefard et al (2012) carried out research on emotional intelligence and organizational culture and state that principally, it is expected that the creation of emotional intelligence paves the way for the development of organizational culture in an organization.…”
Section: Emotional Intelligence and Job Performance Of Employees In An Organizationmentioning
confidence: 99%